2015
DOI: 10.17576/jsm-2015-4407-14
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Tualang Honey on Human Periodontal Ligament Fibroblast Proliferation and Alkaline Phosphatase Level

Abstract: Previous studies on honey have shown its potential as an alternative approach in optimizing medical resources for periodontal treatment. However, to date, there has been no study published on the effects of honey on human periodontal ligament fibroblasts (HPDLFs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…While osteoblast and fibroblast cell migration were represented by the length of the wound, the registered values of wound length were (324.7, 336.4, 547) and (308.3, 464.2, 1032) respectively in 48 h (Tables 7 , 11 ). This aligns with previous research showing that Tualang honey stimulates fibroblast cell proliferation at low concentrations (0.02%) but inhibits it at high concentrations [ 57 ]. Additionally, low concentrations of Pasture honey and Manuka honey have been found to activate phagocytes and stimulate lymphocyte proliferation which promotes wound healing [ 58 ].…”
Section: Discussionsupporting
confidence: 92%
“…While osteoblast and fibroblast cell migration were represented by the length of the wound, the registered values of wound length were (324.7, 336.4, 547) and (308.3, 464.2, 1032) respectively in 48 h (Tables 7 , 11 ). This aligns with previous research showing that Tualang honey stimulates fibroblast cell proliferation at low concentrations (0.02%) but inhibits it at high concentrations [ 57 ]. Additionally, low concentrations of Pasture honey and Manuka honey have been found to activate phagocytes and stimulate lymphocyte proliferation which promotes wound healing [ 58 ].…”
Section: Discussionsupporting
confidence: 92%
“…The finding showed that 0.02% Tualang honey concentration stimulated a higher proliferation rate than the control. However, at a higher concentration of Tualang honey (5%), the cells became rounded and floating, indicating that a higher honey concentration could inhibit cell proliferation [ 98 ].…”
Section: Cell Migration and Proliferation On Honey-based Wound Dressingsmentioning
confidence: 99%